Number 38 (March 1999) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 1999)
(March 1999) - Retention of passive integrated transponder (PIT) tags for individual identification of warmwater stream fishes. By Carol E. Johnston and Elizabeth B. Smithson Laboratory observations of spawning behavior in two species of snubnose darters, Etheostoma colorosum and E. tallapoosae. By Carol E. Johnston, Nathan A. Farnau, Henry L. Bart and Amanda K. Howard Minutes, Business Meeting, 24th Annual Meeting, Southeastern Fishes Council Regional Southeastern Fishes Council Reports News Notes
Keywords: passive integrated transponder; PIT; tags; fishes; warmwater stream; spawning; snubnose darters; etheostoma colorosum; e. tallapoosae